Two Decades of Reform : The Changing Organization Dynamics of Chinese Industrial Firms - Yusuf, Shahid; Nabeshima, Kaoru (World Bank, Washington, DC, 2012)
Since the early 1980s, China has begun gradually integrating with the global system. In doing so the country has moved toward its own unique brand of market socialism, which recognizes private ownership, and is adopting market institutions and pursuing industrial change within the framework of an urban economic environment. The process of transition has now permeated every corner of Chinese life and no organization has been left untouched. Yet industrial organization in China-especially in the state sector-has been slow to shed many of the distinctive structural characteristics of the old line Maoist era state enterprises. The main prong of the industrial strategy in support of urban change is ownership reform that transforms state-owned enterprises into corporate entities with majority state ownership or places them wholly in private hands, in the process also bolstering the incentives for and the dynamism of the private sector. While the central government spearheads the ownership reform initiative, in the majority of cases the actual implementation is in the hands of municipal, county, and prefectural governments that must coordinate their efforts with other factors influencing urban changes. This paper situates industrial change in China within the context of urban development and examines the interplay of broad reform strategy with local implementation, and its actual practice by the reformed firms.